Villous adenoma of gallbladder in a patient with systemic lupus erythematosus - Yuyun Xu; Jianhua Yuan; Vincent Chong; Zhongxiang Ding (Journal of Research in Medical Sciences, 2012)
Villous adenomas occur most frequently in the rectum and colon. These tumors are rarely seen in the gallbladder. We report a case of gallbladder villous adenomas in a 69-year-old patient who has systemic lupus erythematosus (SLE). The patient was admitted for investigation of a gallbladder mass. Ultrasonography, computed tomography, and magnetic resonance imaging showed two well-circumscribed lobulated masses in the gallbladder. Open cholecystectomy was performed and histological examination revealed typical features of villous adenoma. This report describes the first case of villous adenomas of gallbladder with SLE, and documents its imaging findings comprehensively.